STUDENTS’ PERCEPTIONS OF USING ANIMATION VIDEO IN LISTENING COMPREHENSION AT MA CENDEKIA BANGSA PEKANBARU - Riri Fauzana; Siti Nabiilah Syazlika (State Islamic University of Sultan Syarif Kasim Riau, 2026)
This research aimed to describe students’ perceptions of using animation video in listening comprehension at MA Cendekia Bangsa Pekanbaru. The study employed a descriptive quantitative design and involved 44 tenth-grade students in the 2025/2026 academic year selected through total sampling. Data were collected through a 20-item questionnaire organized into five aspects: perceived usefulness, perceived ease of understanding, student engagement, motivation and interest, and perceived effectiveness. The questionnaire used a four-point Likert scale and was tested through Pearson Product Moment validity and Cronbach’s Alpha reliability analysis. All items were valid, and the reliability coefficient was 0.826, indicating that the instrument was reliable. The data were analyzed using descriptive statistics by calculating percentages and mean scores. The findings showed that students had positive perceptions of using animation video in listening comprehension, with an overall mean score of 3.04. Motivation and Interest and Perceived Effectiveness obtained the highest mean scores (3.09), followed by Perceived Usefulness (3.02), while Perceived Ease of Understanding and Student Engagement each obtained a mean score of 3.00. These findings indicate that animation video positively supports listening comprehension by enhancing students’ understanding, engagement, motivation, and learning experience.